Peran Guru Bimbingan Konseling Dalam Pengelolaan Perilaku Bullying Di SMK Negeri 2 Bengkulu Selatan - Waras Adi Putra (UNIVERSITAS BENGKULU, 2023)
The purpose of this study is to describe the role of guidance counselor in bullying behavior management in the country of 2 southern bengkulu. These research methods are qualitative with a descriptive approach. This research data collection technique is (1) observation, (2) interview, and (3) documentation. The results of the study are (1) the role of counseling teachers in planning bullying behaviour prevention in general have been applied, (2) counseling counseling counseling roles in dealing with bullying behaviors have also been applied and have a hopeful impact on the theory used in the study,, (3) the role of counseling teachers in evaluating bullying behavior can also be said to be a decline, (4) although there are a number of obstacles that counseling teachers overcome bullying behaviors but those barriers can be handled by counseling counseling teachers and school guidance.